Neonatal Mortality in Peru by 2030, departmental projections with an equity approach - Avila, Jeannette (2023)
Introduction: The decline in neonatal mortality is progressive in Peru and around the world, but it is unequal between rich and poor or between urban and rural populations. Objective: To project the national and departmental neonatal mortality rate (NMR) to 2030 and measure the inequality gaps of the indicators within departments. Materials and methods: An ecological observational study was conducted to calculate the national and departmental NMR to 2030 by applying the "algorithm for obtaining SDG3 targets" based on the NMR for the period 2012 to 2021 estimated with death certificates. Results: It was found that by 2030, Peru's average NMR could be reduced by 12%, from 8.81 in 2021 to 7.78 neonatal deaths per 1000 live births. Within the country, Huancavelica, Puno, Cusco, Amazonas and Ayacucho would have the highest weighted NMR, going from 14.62 to 12.20, and in the departments of Tacna, Moquegua, Lima, Callao and Ica, with the lowest weighted U5MR, the NMR would go from 6.13 to 5.78. Absolute inequality in the NMR would be reduced by 24%, from 8.49 to 6.42, while relative inequality would remain at 2. Conclusions: A slow reduction in neonatal mortality is projected for 2030, with wide inequality gaps between departments and a significant reduction in NMR only in some departments. Prioritizing preventive interventions will be required to reduce early and late neonatal mortality, avoidable neonatal mortality and prematurity.